The impact of morbid obesity on cardiac structure and function in pregnancy - Fernandes, Nicole Lucy (Department of Anaesthesia and Perioperative Medicine, 2019)
Background: The increasing prevalence of obesity worldwide is a major threat to global health. Structural and functional changes in the heart are well documented for obesity as well as for pregnancy, but there is limited literature on the impact of obesity on cardiac function in pregnancy. We hypothesized that cardiac maladaptation to pregnancy occurs more frequently in otherwise healthy morbidly obese pregnant women than in pregnant women of normal body mass index (BMI). Methods: This prospective cohort study was performed in two referral maternity units in Cape Town, South Africa, over a 3-month period. Forty morbidly obese pregnant women (BMI ≥40 kg.m⁻²) (Group O) were compared to 40 pregnant women of BMI 30 kg.m⁻² (Group N). Cardiac structure and function were assessed by transthoracic echocardiography, according to the recommendations of the British Society of Echocardiography. Results: Acceptable echocardiographic images were obtained in all obese women. Statistical significance was defined as P< .005 after applying the Bonferroni correction for multiple comparisons. Mean [SD] mean arterial pressure was higher in Group O (91 [8.42] vs 84 [9.49] mmHg, P<0.001). There were no between-group differences in heart rate, cardiac output, or cardiac index (84 [12] vs 79 [13] beats.min⁻¹, P=0.103; 5447 [1048] vs 4740 [1183] mL.min⁻¹, P=0.006; 2551 [474] vs 2729 [623] mL.min⁻¹.m⁻², P=0.156, respectively). Stroke volume index was lower, and left ventricular mass higher in Group O (30.14 [4.51] vs 34.25 [7.00] mL.m⁻², P=0.003; 152 [24] vs 115 [29] g, P<0.001). Isovolumetric relaxation time was significantly prolonged in Group O (73 [15] vs 61 [15] milliseconds, P<0.001). The septal tissue Doppler index E' sept was lower in Group O (9.08 [1.69] vs 11.28 [3.18], P<0.001). There were no between- group differences in E' average (10.7 [2.3] vs 12.0 [2.7], P=0.018), or E/E' average (7.85 [1.77] vs 7.27 [1.68]). Conclusion: Obese pregnant women had a similar cardiac output and cardiac index to those with normal BMI. Their increased left ventricular mass and lower stroke volume index could indicate a limited adaptive reserve. Obese women had minor decreases in septal left ventricular tissue Doppler velocity, but the E/E' average values did not suggest clinically significant diastolic dysfunction.